Evaluative Study of OSH Management System in Civil and Mechanical Works of the 150 kV Raha Substation Project - Afiah, Indah Nur; Shiber, Nahridzah Mahjubuh; Sitorus, Mentari S.; Ibrahim, Zulfadli; Muhibuddin, Andi Firman (Universitas Negeri Makassar, 2025)
The construction of substations is one of the most crucial electrical projects in the development of infrastructure and economic growth, to ensure a stable, reliable, and equitable supply of electricity. Electrical construction projects inherently present significant occupational safety and accident risks, ranging from exposure to high voltage to incidents involving heavy equipment. In Indonesia, the Occupational Safety and Health (OSH) Management System known as SMK3 is mandated by Government Regulation (PP) No. 50 of 2012, and serves as the national framework for mitigating these dangers. The goal for implementing this system is to prevent and minimize human and financial losses, including lost work hours and declining productivity, thereby supporting more effective and efficient operational performance. In this study, the implementation of SMK3 on the 150 kV Raha Substation project was evaluated using a descriptive qualitative method with employing data collection instruments that included interviews, field observations, and a checklist of questions based on the audit criteria elements outlined in applicable regulations. The implementation of SMK3, based on 166 audit criteria in the Raha 150 kV Substation construction project, as per PP No. 50 of 2012, achieved a compliance rate of 92.17% (153 criteria compliant and 13 criteria non-compliant), categorized as satisfactory category. From the analysis of respondent interviews and field observations, it was found that the main factors causing obstacles to the optimal implementation of OSH in general are low employee understanding, budget constraints, lack of standardization among subcontractors, and disparities in employee competencies.